Analisa Head Loss Akibat Percabangan Pada Sambungan Reducing T Dengan Variasi Diameter Penampang - Lana, Kadek; Salimin, Salimin; Sisworo, Raden Rinova (Teknik Mesin Universitas Halu Oleo, 2020)
Head loss is a phenomenon of flow losses in the piping system. Head loss is very detrimental in fluid flow, because it can reduce the efficiency of fluid flow. This study aims to determine how much the value of head losses (hT) is that occurs in the reducing T pipe connection with diameter variations on the pipe branch 0.0254m (1 inch), 0.019m (3/4 inch), 0.0127m (1/2 inch). This research was carried out experimentally by measuring the branching flow of the flowing fluid by recording the time and volume of water that had entered the measuring tank, then reading the preasure on the manometer. The results showed that the increase in flow rate (Q) was directly proportional to the head loss (hT). Flow greatly affects the size of the Reynolds number of the three connections, the lowest total head loss occurred in the 1-inch reducing T pipe connection with a value between 0.1715 m- 0.2814 m and the highest total head loss occurred in the reducing T inch pipe connection with a value between 0.4110 m- 0.5867 m.Keyword: Reynold Numbe, debit, head Loss